A model‐based framework for automatic generation of a pattern language verifier. (24th August 2017) - Rouhi, Alireza; Zamani, Bahman
Summary: Design patterns solve recurring design problems. One of the best practices, to solve a whole problem in a specific context, is to apply patterns in the form of a collection of related patterns, ie, a pattern language (PL). However, with the rapid growth of the number of patterns and their interrelationships in PLs and because manual verification of the applied PLs is a tedious and error‐prone task, when designing in PL‐based fashion, there is a need for tool support to verify the applied PLs. In our previous work, aimed at automating the development process of PL verification tools, a PL formalism was presented. This paper, based on the presented formalism, describes a framework called Pattern Language Verifier Generator (PLVGen) that automatically generates a pattern language verifier (PLV) for any given PL assuming its constituent patterns are represented in the Unified Modeling Language (UML). Using a modelware approach, two metamodels named pattern language specification language (PLSL) and pattern specification language (PSL) are developed to model the given PL and its patterns, respectively. By getting the models of a PL and its patterns, PLVGen automatically generates an epsilon validation language (EVL) module representing the expected PLV. By launching PLV, the applied PL on a UML model will be verified. To evaluate the applicability of PLVGen in practice, we automatically generated three PLVs. The statistics regarding the generated PLVs, as case studies, illustrate the scalability of PLVGen. Compared with similar tools, the generated PLVs are more portable, transparent, and free of ambiguities.